A new genomic library of melon introgression lines in a cantaloupe genetic background for dissecting desirable agronomical traits. Issue 1 (December 2016) - Perpiñá, Gorka; Esteras, Cristina; Gibon, Yves; Monforte, Antonio; Picó, Belén
Abstract Background Genomic libraries of introgression lines (ILs) consist of collections of homozygous lines with a single chromosomal introgression from a donor genotype in a common, usually elite, genetic background, representing the whole donor genome in the full collection. Currently, the only available melon IL collection was generated using Piel de sapo (var.inodorus ) as the recurrent background. ILs are not available in genetic backgrounds representing other important market class cultivars, such as thecantalupensis . The recent availability of genomic tools in melon, such as SNP collections and genetic maps, facilitates the development of such mapping populations. Results We have developed a new genomic library of introgression lines from the Japanese cv. Ginsen Makuwa (var.makuwa ) into the French Charentais-type cv. Vedrantais (var.cantalupensis ) genetic background. In order to speed up the breeding program, we applied medium-throughput SNP genotyping with Sequenom MassARRAY technology in early backcross generations and High Resolution Melting in the final steps. The phenotyping of the backcross generations and of the final set of 27 ILs (averaging 1.3 introgressions/plant and covering nearly 100 % of the donor genome), in three environments, allowed the detection of stable QTLs for flowering and fruit quality traits, including some that affect fruit size in chromosomes 6 and 11, others that change fruit shape in chromosomes 7 and 11, others that change flesh color in chromosomes 2, 8 and 9, and still others that increase sucrose content and delay climacteric behavior in chromosomes 5 and 10. Conclusions A new melon IL collection in the Charentais genetic background has been developed. Genomic regions that consistently affect flowering and fruit quality traits have been identified, which demonstrates the suitability of this collection for dissecting complex traits in melon. Additionally, pre-breeding lines with new, commercially interesting phenotypes have been observed, including delayed climacteric ripening associated to higher sucrose levels, which is of great interest for Charentais cultivar breeding.